Classification and Clinical Management of Variants of Uncertain Significance in High Penetrance Cancer Predisposition Genes. Issue 4 (5th February 2016) - Moghadasi, Setareh; Eccles, Diana M.; Devilee, Peter; Vreeswijk, Maaike P.G.; van Asperen, Christi J.
Abstract : In this paper we propose an extension to the existing IARC classification system [Plon et al., 2008 ] and suggest a new communication protocol. The purpose of these recommendations is to improve the clinical management of the counselees by a more precise classification of the variants without causing unnecessary stress for the counselees or additional costs for the health care system, while minimizing the risk of missing pathogenic mutations in clinical practice. ABSTRACT: In 2008, the International Agency for Research on Cancer (IARC) proposed a system for classifying sequence variants in highly penetrant breast and colon cancer susceptibility genes, linked to clinical actions. This system uses a multifactorial likelihood model to calculate the posterior probability that an altered DNA sequence is pathogenic. Variants between 5%–94.9% (class 3) are categorized as variants of uncertain significance (VUS). This interval is wide and might include variants with a substantial difference in pathogenicity at either end of the spectrum. We think that carriers of class 3 variants would benefit from a fine‐tuning of this classification. Classification of VUS to a category with a defined clinical significance is very important because for carriers of a pathogenic mutation full surveillance and risk‐reducing surgery can reduce cancer incidence. Counselees who are not carriers of a pathogenic mutation can be discharged from intensive follow‐up and avoid unnecessary risk‐reducing surgery. By means of examples, we show how, in selected cases, additional data can lead to reclassification of some variants to a different class with different recommendations for surveillance and therapy. To improve the clinical utility of this classification system, we suggest a pragmatic adaptation to clinical practice.